Pt‐Anchored‐Zirconium Phosphate Nanoplates as High‐Durable Carbon‐Free Oxygen Reduction Reaction Electrocatalyst for PEM Fuel Cell Applications. (4th January 2023) - Kumar, Sachin; Yoyakki, Athira; Pandikassala, Ajmal; Soni, Roby; Kurungot, Sreekumar
Abstract: Commercially available platinum‐supported carbon (Pt/C) catalysts are the most widely used oxygen reduction reaction (ORR) electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs). However, inadequate active triple‐phase boundary formation and carbon oxidation in Pt/C during PEMFC operation shorten its lifetime and efficiency. In this direction, a new class of carbon‐free electrocatalysts for ORR is prepared by dispersing Pt nanoparticles on ZrP (Zirconium phosphates) nanoplates. In one case (ZrP@Pt), the Pt nanoparticles are found to be closely distributed and completely covering the ZrP nanoplates, whereas in the second case (Pt/ZrP), the Pt nanoparticles selectively restrict dispersion along the edges of the support. ZrP as the support displays an intrinsic proton conductivity of ≈0.5 × 10 −4 S cm −1 at 70 °C, with an activation energy ( E a ) of 0.19 eV. Pt/ZrP shows better durability after 3000 start‐stop cycles. The mass activity of Pt/ZrP is increased by 4.6 times compared to Pt/C, which exhibits a loss in mass activity by 1.37 times. The single‐cell level validation of ZrP@Pt, Pt/ZrP, and Pt/C as the electrocatalysts in PEMFC at an operating potential of 0.60 V shows the achievable current densities of 0.600, 0.890, and 0.890 A cm −2 . Abstract : A carbon‐free electrocatalyst for oxygen reduction reaction and hydrogen oxidation reaction is developed by decorating Pt nanoparticles on zirconium phosphate (ZrP) nanoplates, which display solid‐state proton conductivity. Due to the solid‐state proton conductivity of the substrate, the active triple‐phase boundary can be built more favorably, and the system as the carbon‐free catalyst exhibits better corrosion resistance and promising performance under the electrochemical conditions.